2008
DOI: 10.1590/s0100-06832008000600029
|View full text |Cite
|
Sign up to set email alerts
|

Alterações no teor de fósforo no solo com aplicação de dejetos líquidos de suínos

Abstract: RESUMOOs dejetos líquidos de suínos servem como fonte de nutrientes às plantas, porém, quando o seu uso é inadequado, podem causar o acúmulo de P no solo, que posteriormente pode ser transferido para o meio aquático, causando eutrofização. Este trabalho teve por objetivo avaliar o potencial de risco de contaminação ambiental com o uso de dejeto líquido de suíno, mensurando as alterações ocorridas no teor de P no solo e nas isotermas de sorção. O trabalho foi realizado na Universidade Federal de Santa Maria, RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
21

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 31 publications
2
38
0
21
Order By: Relevance
“…This probably happened because of the saturation of the most reactive sites of the functional groups on the surface of particles such as clay minerals and oxides, by phosphate (Berwanger et al, 2008;Guardini et al, 2012). The movement of P in the profile probably occurred in soluble form, in view of the high concentrations found in the soil solution (Figure 1), by the water flow through the profile.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This probably happened because of the saturation of the most reactive sites of the functional groups on the surface of particles such as clay minerals and oxides, by phosphate (Berwanger et al, 2008;Guardini et al, 2012). The movement of P in the profile probably occurred in soluble form, in view of the high concentrations found in the soil solution (Figure 1), by the water flow through the profile.…”
Section: Discussionmentioning
confidence: 98%
“…However, when P is added successively and at high rates to the soil, for example by PS application in crop conservation systems such as no-tillage (NT), where the soil is not tilled, the total P content may increase (Berwanger et al, 2008;Lourenzi et al, 2014), and especially the content available to plants, which can be diagnosed by the method of Mehlich-1 (Gatiboni et al, 2008;Guardini et al, 2012). Thus, the saturation of the most avid adsorption sites and a reduction in adsorption energy between phosphate oxygen and functional groups of the surface of oxides and clay minerals are expected, increasing the P concentration in the solution (Guardini et al, 2012;Schmitt et al, 2014); consequently, the P transfer in surface runoff solution to surface waters increases, but also migration in the soil profile by water flow, raising the risk of contamination of subsurface waters, especially in soils with sandy surface texture (Berwanger et al, 2008;Ceretta et al, 2010b;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Losses of P by leaching or surface runoff, when attached to soil colloids, present a risk of degradation of groundwater and surface waters, respectively (Ceretta et al, 2010). Berwanger et al (2008) found that pig slurry application at the surface of an Ultisol soil resulted in nutrient loss by surface runoff, while Djodjic et al (2004) reported nutrient losses by leaching.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Em solos contendo óxidos de Fe e de Al e caulinita a interação do P com o grupo funcional ligado aos cátions (em geral, Fe-OH e Al-OH e grupamento aluminol) nas superfícies das partículas ocorre pelo compartilhamento eletrônico e, portanto, apresenta diferentes graus de energia de ligação (Barrow et al, 1998;Barrow, 1983Barrow, ,1999Berwanger et al, 2008). Assim, quando presentes na superfície, a existência dos grupamentos OH dependerá do pH e da força iônica da solução (Stumm, 1992), bem como do tipo de ligação em coordenação dos grupamentos protonados com o metal na superfície do mineral (Rakovan et al, 1999).…”
Section: Natural E Hm E Gt Sintéticas Para a Região De Baixas Concentunclassified